2-Methacryloyloxyethyl Phosphorylcholine Polymer Coating Inhibits Bacterial Adhesion and Biofilm Formation on a Suture: An In Vitro and In Vivo Study. (1st October 2020) - Kaneko, Taizo; Saito, Taku; Shobuike, Takeo; Miyamoto, Hiroshi; Matsuda, Junpei; Fukazawa, Kyoko; Ishihara, Kazuhiko; Tanaka, Sakae; Moro, Toru
Abstract : Initial bacterial adhesion to medical devices and subsequent biofilm formation are known as the leading causes of surgical site infection (SSI). Therefore, inhibition of bacterial adhesion and biofilm formation on the surface of medical devices can reduce the risk of SSIs. In this study, a highly hydrophilic, antibiofouling surface was prepared by coating the bioabsorbable suture surface with poly(2-methacryloyloxyethyl phosphorylcholine (MPC)-co-n-butyl methacrylate) (PMB). The PMB-coated and noncoated sutures exhibited similar mechanical strength and surface morphology. The effectiveness of the PMB coating on the suture to suppress adhesion and biofilm formation of methicillin-resistant Staphylococcus aureus and methicillin-susceptible Staphylococcus aureus was investigated both in vitro and in vivo . The bacterial adhesion test revealed that PMB coating significantly reduced the number of adherent bacteria, with no difference in the number of planktonic bacteria. Moreover, fluorescence microscopy and scanning electron microscopy observations of adherent bacteria on the suture surface after contact with bacterial suspension confirmed PMB coating-mediated inhibition of biofilm formation. Additionally, we found that the PMB-coated sutures exhibited significant antibiofouling effects in vivo . In conclusion, PMB-coated sutures demonstrated bacteriostatic effects associated with a highly hydrophilic, antibiofouling surface and inhibited bacterial adhesion and biofilm formation. Therefore, PMB-coated sutures could be a new alternative to reduce the risk of SSIs.